Two chemically distinct root lignin barriers control solute and water balance - Guilhem Reyt (Nature Portfolio, 2021)
Defects in the Casparian strip, a fine band of lignin that seals root endodermal cells and plays roles in nutrient homeostasis, activate a signaling pathway leading to over-lignification. Here, the authors show that this process leads to the deposition of compensatory lignin that is chemically distinct from Casparian strip lignin.